Fibronectin enhances attachment of human adipose-derived mesenchymal stem cells into polytetrafluoroethylene patch during surgical closure of the atrial and ventricular septal defect - I Gde Rurus Suryawan; Anudya Kartika Ratri; Andrianto Andrianto; Meity Ardiana; Ricardo Adrian Nugraha (Wolters Kluwer Medknow Publications, 2023)
Background : Polytetrafluoroethylene (PTFE) patch is commonly used during surgical closure for atrial septal defect (ASD) and ventricular septal defect (VSD). However, this patch has several limitations such as its inability to grow or remodel, especially in children and young adults. To tackle these limitations, we have tried to use fibronectin and human adipose-derived mesenchymal stem cells (hAMSCs) in the PTFE patch. Objective : To understand the impact of fibronectin to enhance hAMSCs cell-to-cell adherence and cell-to-patch surface attachment into PTFE patches used in the surgical closure of ASD or VSD. Materials and Methods : The hAMSCs were plated and fixated with 15 mL methanol and cluster of differentiation (CD) 90+, CD105+, and CD45 - antibodies were labeled with fluorescein isothiocyanate, rinsed with phosphate-buffered saline, and analyzed under a fluorescence microscope. Fibronectin solution (0.1%) was used to soak patch scaffolds for approximately 2-h duration and then dried for 20 min in the treatment group. The samples were examined with a scanning electron microscope (SEM). Results : SEM examination showed incomplete attachment of the cells even after 10 days in the control group at 1.14 ± 1.13. In contrast, the treatment group showed more cells attached to the patch surface at 31.25 ± 13.28 (P ≤ 0.0001). The observation at 5 days was 17.67 ± 20.21, at 7 days was 12.11 ± 10.94, and at 10 days was 18.83 ± 23.25. There was no significant statistical difference in mean cell per view among each treatment group (P = 0.802). Conclusion : Our work demonstrates that fibronectin has a positive impact on hAMSC attachment seeded onto the PTFE patch. These properties, in combination with their developmental plasticity, have generated tremendous interest in regenerative medicine.